Relationship of p53 Mutations to Epidermal Cell Proliferation and Apoptosis in Human UV-Induced Skin Carcinogenesis - Janine G. Einspahr; David S. Alberts; James A. Wameke; Paul Bozzo; Jenny Basye; Thomas M. Grogan; Mark A. Nelson; G. Tim Bowden (Neoplasia: An International Journal for Oncology Research, 1999)
Human skin is continually subjected to UV-irradiation with the p53 gene playing a pivotal role in repair of UV-induced DNA damage and apoptosis. Consequently, p53 alterations are early events in human UV-induced skin carcinogenesis. We studied 13 squamous cell carcinomas (SCC), 16 actinic keratoses (AK), 13 samples adjacent to an AK (chronically sun-damaged), and 14 normal-appearing skin samples for p53 mutation, p53 immunostaining (IHC), apoptosis (in situ TUNEL and morphology), and proliferation (PCNA). The frequency of p53 mutation increased from 14% in normal skin, to 38.5% in sun-damaged skin, 63% in AK, and 54% in SCC. p53 IHC increased similarly. Apoptosis (TUNEL) increased from 0.06 ± 0.02%, to 0.1 ± 0.2, 0.3 ± 0.3, and 0.4 ± 0.3 in normal skin, sun-damaged skin, AK, and SCC, respectively. Apoptosis was strongly correlated with proliferation (i.e., TUNEL and PCNA, r = 0.7, P < 0.0001), and proliferation was significantly increased in the progression from normal skin to SCC. Bax was significantly increased in SCC compared to AK. These data imply that apoptosis in samples with a high frequency of p53 mutation may not necessarily be p53-dependent. We suggest that there is a mechanism for apoptosis in response to increased cellular proliferation that is p53-independent.